WORD FORMATION PROCESS FOUND in LESTY KEJORA’S CAPTION on INSTAGRAM - Nur Halimah Lubis; Emeliya Sukma Dara Damanik; Aulia Fatin Pakpahan; Nabilla Fauza Nasution; Ega Viorenti Nabilla (STKIP Budidaya Binjai, 2022)
This study aims to decipher Word formation Process Found in Lesty Kejora'scaption on Instagram